2001
DOI: 10.1007/s002040100213
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of PCB-126 in European flounder ( Platichthys flesus ) with emphasis on histopathology and cytochrome P4501A induction in several organ systems

Abstract: A series of experiments was set up to elucidate the effects of pollution on marine and estuarine fish health, since the European flounder (Platichthys flesus) has shown a relatively high prevalence of (pre)neoplastic liver lesions and lymphocystis virus disease in Dutch coastal and estuarine waters. The hypothesis of a causal relationship between pollution and the above-mentioned diseases was supported by results from semi-field experiments. Therefore several laboratory experiments were carried out to substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…In fish the m ost im portant organs in the immune function are the head kidney, thym us and spleen. In European floun der (Platichthysflesus) exposed to 50 mg PCB-126/kg (Grinwis et al, 2001) thym us atrophy was reported suggesting an impact on the specific resistance against infectious diseases (viral, bacterial, and parasitical) in the field situation. The reported effects of PCBs on the immunologically im portant spleen (Taysse et al, 1998) can be quite different, as in some studies a reduction of the spleen w eight is observed (Nakata et al, 2002) w hile in other studies a spleen hyper trophy was reported (Greichus et al, 1975).…”
Section: Effects On Organ Weightsmentioning
confidence: 99%
“…In fish the m ost im portant organs in the immune function are the head kidney, thym us and spleen. In European floun der (Platichthysflesus) exposed to 50 mg PCB-126/kg (Grinwis et al, 2001) thym us atrophy was reported suggesting an impact on the specific resistance against infectious diseases (viral, bacterial, and parasitical) in the field situation. The reported effects of PCBs on the immunologically im portant spleen (Taysse et al, 1998) can be quite different, as in some studies a reduction of the spleen w eight is observed (Nakata et al, 2002) w hile in other studies a spleen hyper trophy was reported (Greichus et al, 1975).…”
Section: Effects On Organ Weightsmentioning
confidence: 99%
“…Dube and Hosetti (2010) stated that pronounced secretion of mucus layer over the gill lamellae observed during cyanide stress curtails the diffusion of oxygen, which ultimately reduce the oxygen uptake by the animal. Also, it was said that if gills were destroyed due to xenobiotic chemicals (Grinwis et al, 1998) or the membrane functions are disturbed by a changed permeability (Hartl et al, 2001), oxygen uptake rate would rapidly decrease. Thus, it can be inferred that decrease oxygen consumption observed might be as a result alteration in membrane or damage to gills membrane by potassium cyanide molecules of exposed fish specimens.…”
Section: Resultsmentioning
confidence: 99%
“…The organs possess immune Speciation Analysis and Environment and hematopoietic functions, and are essential for fish health. Grinwis et al 37 noted a significant reduction of thymus induced by TBTO in Platichthys flesus. Thymus atrophy by TBTO has been demonstrated in Poecilia reticulata and Oritias latipes.…”
Section: Discussionmentioning
confidence: 96%